2019
DOI: 10.1017/wsc.2019.73
|View full text |Cite
|
Sign up to set email alerts
|

A new race of sunflower broomrape (Orobanche cumana) with a wider host range due to changes in seed response to strigolactones

Abstract: Broomrapes (Orobanche and Phelipanche species, Orobanchaceae) are obligate root parasites of dicotyledonous plants. This taxonomic group includes seven weedy parasites of agricultural crops that damage vegetables, sunflower (Helianthus annuus L.), and legumes. Processing-tomato (Solanum lycopersicum L.) fields in Israel have been recently found infested with a new broomrape, first identified as nodding broomrape (Orobanche cernua Loefl.) based on its host. However, its morphology resembled the closely related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Strigolactones do not seem to play this role in the sunflower-broomrape interaction, but in other host-parasite systems where STLs do not occur, they could have a similar chemotropic function. In this context, it could be of particular interest to see the chemotropic reaction of a recently detected new race of sunflower broomrape (Dor et al, 2020), which also attacks Solanaceae, for which STLs have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Strigolactones do not seem to play this role in the sunflower-broomrape interaction, but in other host-parasite systems where STLs do not occur, they could have a similar chemotropic function. In this context, it could be of particular interest to see the chemotropic reaction of a recently detected new race of sunflower broomrape (Dor et al, 2020), which also attacks Solanaceae, for which STLs have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In poorly diversified crop consequences (i.e. tobacco monoculture or rapeseed-wheat rotation), this ability can result in the selection of populations that are highly adapted to the crop, as observed on other parasitic plants (Dor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in response to germination stimulant compounds cause host specificity between these species. The emergence of O. cernua is only stimulated by strigolactones (orobanchol, 5-deoxystrigol, 2 0 -epiorobanchol, and GR24), but O. cumana responds to dehydrocostus lactone and GR24 (Dor et al 2020). While O. cernua is a significant component of the Orobanche complex in solanaceous crops (particularly tomato, tobacco, and eggplant) in other countries (Parker 2009), there are no reports of its occurrence in Iran.…”
Section: Orobanche Cumana Wallrmentioning
confidence: 99%
“…Usually, morphological differences are used to identify various broomrape species (Parker and Riches 1993). However, these differences are not clear enough, and the use of molecular markers such as simple sequence repeats (SSR) of nuclear and plastid genomes has been suggested (Dor et al 2020;Westwood et al 2012).…”
Section: Orobanche Cumana Wallrmentioning
confidence: 99%